Technological pedagogical and content knowledge with student course engagement framework for virtual classroom in Malaysia higher education - Lai, Daniel; Lew, Sook Ling; Ooi, Shih Yin (Frontiers in Computer Science, 2025)
IntroductionRecent educational transformations have caused teachers to face difficulties in learning and adopting online tools to establish student course engagement (SCE). Thus, three significant problems are outlined in this research: lack of SCE in virtual classrooms, ineffective technology integration into pedagogy and lack of self-proficiency in technologies to enhance students’ academic performance. Moreover, three research questions emerged regarding the SCE, the teachers’ proficiency in technological, pedagogical and content knowledge (TPACK) for teaching, and the students’ academic performance. Hence, a framework that adopted the TPACK framework and the Student Course Engagement Questionnaire (SCEQ) was developed.MethodsA developed mobile interactive system (MIS) integrated into the virtual classroom, determining factors that contributed to improving SCE, assessing teachers’ proficiency in teaching with technology from students’ perspectives, and assessing SCE and academic performance improvement. A quasi- experimental design was employed in the current research to collect quantitative data and for statistical analysis. Pretest-posttest experiments were conducted with 80 local university undergraduate students from two different groups, with and without developed MIS integration. Homogeneity among the participants was assured by distributing a pre-knowledge checking test before the actual experiment began. The TPACK and SCEQ surveys were distributed for further analysis.ResultsThe SCE and TPACK R2 values are 0.111 and 0.748, respectively, indicating that SCE has low predictive power. However, the experiment results indicate that teachers’ proficiency in TPACK has a medium effect on SCE. Additionally, the student’s academic performance has shown significant improvement.DiscussionMoreover, the current research suggested that content and technological knowledge are more vital than pedagogical knowledge in the virtual classroom. Therefore, the current research results indicated that the integration of developed MIS improves students’ SCE and academic performance significantly. The integration of the developed MIS in the virtual classroom also enhanced teachers’ proficiency in TPACK. Moreover, the change of perspectives when examining teachers’ TPACK proficiency provides more valuable insights as students benefited from the lessons directly.